Special aspects of transferring the ball by Leicester City players in the matches of the 2015–2016 Premier League season - Перцухов, Андрей (Slobozhanskyi Herald of Science and Sport, 2017)
Andrii Pertsukhov Purpose: to reveal quantitative and qualitative indicators of transferring the ball by Leicester City players in the matches of the 2015–2016 Premier League season. Material & Methods: analysis of scientific and methodological literature, registration of technical and tactical actions (transfer of the ball), methods of mathematical statistics. It carried out a study of competitive activity command "Leicester City" – the champion of Premier League season 2015–2016. Results: quantitative and qualitative indicators of transferring the ball by Leicester City players in the matches of the 2015–2016 Premier League season are presented. Conclusion: as a result of the research of the Leicester City team transferring the ball in games that ended in victory, draw and defeat of significant differences were not revealed. Differences in some quantitative and qualitative indicators of transferring the ball in home and away games, in games of the first and second round of the championship.